Meningkatkan Kemampuan Shooting Bola Basket Dengan Menggunakan Permainan Target Pada Siswa Kelas XI SMA Negeri 12 Bungo - Irman Irman (Jurnal Muara Olahraga, 2023)
Abstract This research was motivated by the difficulties of students shooting into the ring and the students' throwing was still too weak so the balls thrown were not quite on target. Seeing the problems that occur in class XI students at SMA Negeri 12 Bungo, a more effective and efficient learning approach is needed. An approach that leads to how students are trained to be serious, motivated and accustomed to throwing throwing objects precisely to a predetermined place. The learning approach is with a target game. The study used a Classroom Action Research design which was carried out in two cycles, each cycle consisting of planning, implementing actions, observing and reflecting. The subjects of this study were 20 students of class XI at SMA Negeri 12 Bungo. Data on basketball learning outcomes were obtained through performance tests, observation sheets were used to collect data on student activities in participating in the basketball learning process. The results of this study were obtained based on an assessment of the ability to shoot basketball using target games in class XI students at SMA Negeri 12 Bungo. From this aspect of the assessment, the percentage of students' completeness scores in cycle I was 40%. The results of the assessment of the aspects of learning basketball in the first cycle showed that students achieved the completeness criterion or a score of > 70. There was a significant increase from the conditions in cycle I to cycle II. The results of the basketball learning assessment obtained from cycle II were as many as 18 students who passed. While in the cycle II stage, the percentage of completeness is 90%. Of the 20 students, 18 were declared to have completed, only 2 students had not achieved completeness. Based on the results of the study, it was concluded that learning basketball through target games can improve student learning outcomes. And for Physical Education teachers, they can apply learning effectively according to Physical Education lessons, especially in learning basketball. Keywords: Target Game, Basketball, Learning